2019
DOI: 10.1002/jbio.201900095
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of corneal epithelial thickness in glaucomatous patients using anterior‐segment optical coherence tomography

Abstract: The corneal epithelium represents one of the main structures that undergo degenerative alterations due to antiglaucomatous therapy. Chronic glaucoma therapy containing benzalkonium chloride induces epithelial cellular changes and inflammatory infiltration that in turn causes ocular surface changes resulting in ocular discomfort. Also, age‐related changes can involve the tear film stability and the corneal epithelium surface with reduction of microvilli. The objective of this study is to gain insights about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 28 publications
(38 reference statements)
2
14
0
1
Order By: Relevance
“…Each CET map was divided into 17 sectors: a central sector 0 to 2 mm in diameter, 8 paracentral sectors from 2 to 5 mm in diameter and 8 peripheral sectors from 5 to 6 mm in diameter. [ 13 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each CET map was divided into 17 sectors: a central sector 0 to 2 mm in diameter, 8 paracentral sectors from 2 to 5 mm in diameter and 8 peripheral sectors from 5 to 6 mm in diameter. [ 13 ]…”
Section: Methodsmentioning
confidence: 99%
“…Each CET map was divided into 17 sectors: a central sector 0 to 2 mm in diameter, 8 paracentral sectors from 2 to 5 mm in diameter and 8 peripheral sectors from 5 to 6 mm in diameter. [13] 2.3 | Scheimpflug densitometry CD analysis was provided as an add-on to the standard software of the Pentacam HR type 70 900 with a rotating Scheimpflug camera (Oculus Optikgeräte GmbH). The measurement protocol took a series of 25 images (1003 × 520 pixels) over different meridians with a uniform blue light source.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Differently, a recent study did not find significant differences in corneal epithelial thickness among patients under different types and durations of treatment, while the only factor influencing corneal epithelial thickness was represented by age [ 77 ]. In a similar study, Dogan et al [ 78 ] reported that there was no significant correlation between corneal thickness and glaucoma type, duration of therapy, number of drugs, and daily drops.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Discording results in the corneal thickness parameters at AS-OCT o with regard to the number of drugs used [ 76 , 77 , 78 ]…”
Section: Medical Treatmentmentioning
confidence: 99%